FTA supports better integration of forestry and agroforestry in national adaptation plans - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The guidelines, co-published with FAO are intended to be used by national planners and decision–makers working on climate change issues in developing countries and authorities and experts who are contributing to climate change adaptation and NAP formulation and implementation.